MARKETING PLAN SEBAGAI UPAYA PENCAPAIAN STRATEGI PEMASARAN PERUSAHAAN JANGKA PANJANG - Triastity, Rahayu (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
ABSTRACT Marketing plan is an important element in a company business plan. Marketing plan is conducted annually focused on implementation of decision dealing with marketing variable mix that is product, price, distribution, and promotion. Marketing plan must be monitored regularly especially in the beginning stage, as part of business plan. Marketing plan provides data for the company about neighborhood description, tactics and specific objectives that will be achieved. Marketing plan also describes a measurable standard norm, provides a base for the next plan, as well arranges specific marketing action, which is aimed to encourage along term factory strategy achievement. While the Marketing plan process consists of five stages: 1) Conduct a situation analysis, 2) Develop marketing objectives, 3) Determine positioning and deferential advantage, 4) Select target market and measure market demand, 5) Design a strategic marketing mix. Keywords: marketing mix marketing plan, marketing strategic, market response.